Scanning of Prospective Investment Opportunities for a Regional Venture Capital Fund - Mole, Richard James; Mu, Jasmine Chao-wen; Al Shuaibi, Khalid (2007)
This study's aim was to identify start up or early stage companies in the East Midlands region with potentially high growth prospects eligible for equity financing from a government backed venture capital fund (East Midlands Early Growth Fund). A proactive approach was taken for deal generation, rather than a reactive method typically adopted by conventional venture capitalists (VCs).